Pengaruh Kecerdasan Emosional terhadap Hasil Belajar Matematika Siswa Kelas X SMA Swasta Muhammadiyah Maumere - Veramus Nong Sama; Agustinus Angelaus Ete; Agnesia Bergita Anomeisa (International Forum of Researchers and Lecturers, 2025)
This study aims to determine the effect of emotional intelligence on student learning outcomes in class X mathematics at Muhammadiyah Maumere Private High School. The population of this study were students of class X IPA I and IPA 2, totaling 39 students. The sample in this study consisted of 39 students. Data collection was carried out by distributing questionnaires related to emotional intelligence on the results of learning mathematics in class X SMA Muhammadiyah Maumere Private High School Based on the results of the analysis with a significant level of 5%, it can be concluded (1) There is a significant effect of emotional intelligence for the experimental class on mathematics learning outcomes (2) There is an insignificant effect of emotional intelligence for the control class on mathematics learning outcomes for Muhammadiyah Maumere Private High School students.